Adjuvanting an inactivated influenza vaccine with flagellin improves the function and quantity of the long-term antibody response in a nonhuman primate neonate model - Holbrook, Beth C. (Vaccine, 2016)
Young infants are at significantly increased risk of developing severe disease following infection with influenza virus. At present there is no approved vaccine for individuals below the age of six months given previous studies showing a failure of these individuals to efficiently seroconvert. Given the major impact of influenza on infant health, it is critical that we develop vaccines that will be safe and effective in this population. Using a nonhuman primate (NHP) model, we have evaluated the ability of an inactivated influenza virus vaccine adjuvanted with flagellin to result in long term immune responses in neonates. To evaluate this critical attribute, neonate NHP were vaccinated and boosted with inactivated influenza virus in combination with either flagellin or a mutant inactive flagellin control. Our studies show that inclusion of flagellin resulted in a significant increase (5-fold, p=0.04) in influenza virus-specific IgG antibody at 6 months post-vaccination. In addition, the antibody present at this late time was of higher affinity (2.4-fold, p=0.02). Finally a greater percentage of infants had detectable neutralizing antibody. These results support the use of flagellin in neonates as an adjuvant that promotes long-lived, high affinity antibody responses.